CARD9 deficiency improves the recovery of limb ischemia in mice with ambient fine particulate matter exposure - Zhu, Qiang; Liu, Xuanyou; Wu, Hao; Yang, Chunlin; Wang, Meifang; Chen, Feng; Cui, Yuqi; Hao, Hong; Hill, Michael A.; Liu, Zhenguo (Frontiers in Cardiovascular Medicine, 2023)
Background: Fine particulate matter (PM) exposure significantly increases the risk of cardiovascular diseases largely due to increased reactive oxygen species (ROS) production and inflammation. Caspase recruitment domain (CARD)9 plays an essential role in innate immunity and inflammation. The present study was designed to test the hypothesis that CARD9 signaling is critically involved in PM exposure-induced oxidative stress and impaired recovery of limb ischemia. Methods and Results: Critical limb ischemia (CLI) was created in male wildtype C57BL/6 and age matched CARD9 deficient mice with or without PM (average diameter 2.8 μm) exposure. Mice received intranasal PM exposure for one month before creation of CLI and continued for the duration of the experiment. Blood flow and mechanical function were evaluated in vivo at baseline and days 3, 7, 14, and 21 post CLI. PM exposure significantly increased ROS production, macrophage infiltration, and CARD9 protein expression in ischemic limbs of C57BL/6 mice in association with decreased recovery of blood flow and mechanical function. CARD9 deficiency effectively prevented PM exposure-induced ROS production and macrophage infiltration and preserved the recovery of ischemic limb with increased capillary density. CARD9 deficiency also significantly attenuated PM exposure-induced increase of circulating CD11b+/ F4/80+ macrophages. Conclusion: The data indicate that CARD9 signaling plays an important role in PM exposure-induced ROS production and impaired limb recovery following ischemia in mice.